Silver decorated titanate/titania nanostructures for efficient solar driven photocatalysis - Gong, Dangguo (2013)
Photocatalysis has attracted significant interest to solve both the energy crisis and effectively combat environmental contamination. However, as the most widely used photocatalyst, titania (TiO2) suffers from inefficient utilization of solar energy due to its wide band gap. In the present paper, we describe a method to extend the absorption edge of photocatalyst to visible region by the surface plasmon effect of silver. Silver ions are photo-reduced onto the surface of titanate nanotubes, which are synthesized by a conventional hydrothermal method. The as-synthesized Ag/titanate composite is transformed into Ag/titania nanoparticles by annealing at different temperatures. It is found that the interaction of Ag nanoparticles with the supports (titanate/titania) plays a key role for the visible light activity. The samples annealed at low temperature (<350 °C) do not show significant activity under our conditions, while the one annealed at 450 °C shows fast-degradation of methyl orange (MO) under visible light irradiation. The detailed mechanisms are also discussed.